A Review on Test Case Prioritization Technique for Event Sequence Test Cases - Ahmad, Johanna; Baharom, Salmi; Azim Abd Ghani, Abd; Zulzalil, Hazura; Din, Jamilah (International Journal of Engineering and Technology, 2018)
Software testing is a process to verify and validate the correctness of a software product before it is delivered to the customer. Any modifications on the requirements or codes can cause the testing process to be redone all over again. Such occurrences could cause additional time, resources, and cost during testing. Hence, the test case prioritization (TCP) technique has been proposed, with the objective of prioritizing test case sequences and finding faults as early as possible to increase the effectiveness and efficiency of the testing process. Various TCP techniques are available, with the combination of different factors, research area, methodologies, and evaluation metric. This paper summarizes and discusses how the TCP technique can be applied for event sequence test cases. Analysis results from this preliminary study would help the researchers plan for future work, which is to propose an enhancement of the TCP technique for application with event sequence test cases.Â Â